Trends in Weather Conditions and Performance by Age Groups Over the History of the Berlin Marathon - Knechtle, Beat; Valero, David; Villiger, Elias; Alvero-Cruz, José R.; Nikolaidis, Pantelis T.; Cuk, Ivan; Rosemann, Thomas; Scheer, Volker (Frontiers in Physiology, 2021)
The effect of different environmental conditions such as temperature, wind, barometric pressure and precipitation has been well investigated in elite marathoners, but not by age categories (i.e., age group marathoners). The aim of the study was to investigate the potential influence of environmental conditions such as temperature, precipitation and atmospheric pressure on marathon performance in age group marathoners competing in the ‘Berlin Marathon’ from 1974 to 2019. A total of 869,474 valid finisher records were available for analysis, of which 711,136 correspond to males and 158,338 to females. The influence of temperature, atmospheric pressure and precipitation on marathon race times was investigated in age group marathoners grouped in 5-year-intervals. Within the 46 years of Berlin marathons under investigation, there was some level of precipitation for 18 years, and 28 years without any rain. Sunshine was predominant in 25 of the events, whilst in the other 21 years, cloud cover was predominant. Marathon race times were significantly and positively related with age (i.e., older runners were slower than younger runners) where the correlation was higher for males than for females. Marathon race times were significantly and positively correlated with both sunshine duration and daily maximum temperature. The fastest marathon runners (meaning the minimum times) achieved the fastest race times on race days with higher maximum temperatures (i.e., 15-30 °C). Daily maximum temperatures showed an influence on age group marathoners from age group 35-40 years and older. Higher precipitation levels impaired performance across most age groups. In summary, higher daily maximum temperatures (i.e., > 15 °C) and higher precipitation levels impaired performance of master marathoners (i.e., 35-40 years and older) competing in the ‘Berlin Marathon’ in the last 45 years. Master marathoners should start in marathon races with temperatures < 15 °C and no precipitation in order to achieve a fast marathon race time.